Cardinium disrupts Wolbachia-host dynamics in the domestic mite Tyrophagus putrescentiae: evidence from manipulative experiments - Hubert, Jan; Glowska-Patyniak, Eliza; Dowd, Scot E; Klimov, Pavel B (mSystems, 2025)
UNLABELLED: We investigated the tripartite interactions between two intracellular bacterial symbionts, Cardinium and Wolbachia in Tyrophagus putrescentiae. Cultures of Tyrophagus putrescentiae are typically single-infected by one intracellular symbiont. However, co-infection can be experimentally induced by mixing single-infected cultures, resulting in 10% of mite individuals being double-infected (Cardinium + Wolbachia) and a corresponding reduction in host fitness. Here, we assembled the genomes of Cardinium and Wolbachia and analyzed their gene expression in parental single-infected and mixed mite cultures using population-level samples (ranging from 7,500 to 10,000 mites). Wolbachia interacts more extensively with its mite host than Cardinium in single-infected cultures. However, in mixed cultures, (i) Wolbachia exhibited reduced regulation of the host compared with Cardinium; (ii) the gene expression profile of Cardinium shifted, increasing its interactions with the host, whereas the gene expression profile of Wolbachia remained unchanged; and (iii) Wolbachia genes exhibited a loss of interactions with mite gene expression, as indicated by reduced correlations (for example with host MAPK, endocytosis, and calcium signaling pathways). The experiments show that at the mite population level, symbiont infection disrupts gene expression interaction between the two symbionts and their host in different ways. Wolbachia was more influenced by Cardinium gene expression than vice versa. Cardinium can inhibit the growth of Wolbachia by disrupting its interaction with the host, leading to a loss of Wolbachia's influence on mite immune and regulatory pathways. The reasons for responses are due to co-infection or the reduced frequency of Wolbachia single-infected individuals due to the analyses of population-level samples. IMPORTANCE: We found that Cardinium disrupts the interaction between Wolbachia and mite host. In Wolbachia single-infected cultures, strong correlations exist between symbiont and host gene expressions. Interestingly, although Cardinium can also interact with the host, this interaction appears weaker compared with Wolbachia in single-infected cultures. These results suggest that both symbionts affect mite host gene expression, particularly in immune and regulatory pathways. In mixed samples, Cardinium appears to outcompete Wolbachia by disrupting its host interaction. It indicates competition between these two intracellular symbionts in mite populations. Wolbachia belongs to a mite-specific supergroup Q, distinct from the more commonly studied Wolbachia supergroups. As these mite-specific bacteria exhibit pathogen-blocking effects, our findings may have relevance for other systems, such as ticks and tick-borne diseases. The study sheds light on intracellular symbiont interaction within a novel mite-symbiont model.
Keywords: Wolbachia; Symbiosis; genome; Cardinium; Mites; zvířata; mite; Bacteroidetes; gene expression; symbióza; interaction; roztoči; Animals